MOF Catalysts: Zr‐Metal‐Organic Framework Catalysts for Oxidative Desulfurization and Their Improvement by Postsynthetic Ligand Exchange (Small Methods 12/2018). Issue 12 (10th December 2018) - Fu, Guangxia; Bueken, Bart; De Vos, Dirk
Abstract : In article1800203, Dirk De Vos and co‐workers employ Zr‐metal organic frameworks as the catalyst for oxidative desulfurization, which shows the potential of metal‐organic frameworks (MOF) to remove sulfur compounds from fuel. MOFs' topology and its coordination with ligands could affect the number of accessible Lewis acid sites, which play an important role in their catalytic activity.